2017
DOI: 10.1002/tie.21916
|View full text |Cite
|
Sign up to set email alerts
|

What do managers look for in candidates for international assignments?

Abstract: Globalization of business highlights the need for individuals with the right skills and experiences for international assignments. Gender, age, ethnicity, family situation, professional qualifications, past international experiences, as well as psychological characteristics can be counted among the selection criteria of a candidate for such assignments. This current study examines the role of assignment context and selecting manager characteristics in the selection process. First, these candidate characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 86 publications
(128 reference statements)
2
8
0
Order By: Relevance
“…Considering the study findings and the research key questions, two major streams of results exploration and discussion are suggested. First, in what concerns recruitment and staffing approaches to expatriation assignments observed in the multinational business contexts considered by the study, the findings are in part consistent with the existing literature on the topic (Anderson, 2005; Cheng & Lin, 2009; Harris & Brewster, 1999; Kandogan, 2018; Makela et al, 2010; Shen & Lang, 2009; Tungli & Peiperl, 2009; Zhu et al, 2017). The preferential use of internal recruitment options guided or bounded by closed and informal coordination systems and staffing criteria is documented for mature multinational companies and Anglo-Saxon developed economies (Brookfield, 2016; KPMG, 2020; Shen & Lang, 2009; Tungli & Peiperl, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Considering the study findings and the research key questions, two major streams of results exploration and discussion are suggested. First, in what concerns recruitment and staffing approaches to expatriation assignments observed in the multinational business contexts considered by the study, the findings are in part consistent with the existing literature on the topic (Anderson, 2005; Cheng & Lin, 2009; Harris & Brewster, 1999; Kandogan, 2018; Makela et al, 2010; Shen & Lang, 2009; Tungli & Peiperl, 2009; Zhu et al, 2017). The preferential use of internal recruitment options guided or bounded by closed and informal coordination systems and staffing criteria is documented for mature multinational companies and Anglo-Saxon developed economies (Brookfield, 2016; KPMG, 2020; Shen & Lang, 2009; Tungli & Peiperl, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Analytical work was theoretically driven. Expatriate recruitment systems and practices were analysed considering two dimensions: (a) degree of formality and (b) openness/inclusiveness of existing systems (Anderson, 2005; Harris & Brewster, 1999; Kandogan, 2018; Makela et al, 2010; Shen & Lang, 2009; Tungli & Peiperl, 2009). Expatriate willingness screening was driven by the existing expatriate opt-in motivation literature (de Eccher & Duarte, 2016; Dickmann & Baruch, 2011; Doherty & Dickmann, 2009; Froese & Peltokorpi, 2011; Halberger & Brewster, 2009; ; McNulty & Brewster, 2019Mol et al, 2009; Pate & Scullion, 2010; Peltokorpi & Froese, 2009; Suutari & Makela, 2007; Tharenou, 2008; Waxin et al, 2019), and it focused on checking the existence of tensions between structural conditions and personal positionings (Bourdieu, 1972/1990; Costas, 2013; Deleuze & Guattari, 2004; Ehrenberg, 1998; Elliot, 2015; Lindgren & Wåhlin, 2001; Sainsaulieu, 1985), possibly moulding employee motives and opt-in/out decisions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DeLong & Elbeck, 2018; Goleman, Boyatzis, & McKee, 2001;Graf, 2004;Kandogan, 2018), this delicate balance between technical and interpersonal skills has become increasingly important in changing business environments. Therefore, it is vital that human resource practitioners ensure the accurate measurement and assessment of soft skills throughout the recruitment process to ensure the effective evaluation of these skills given their importance in the next normal.…”
Section: Employers Equipping Themselves For the Next Normalmentioning
confidence: 99%
“…One issue that has not been examined in the context of Japanese expatriates is the influence of family on their willingness or the decision to undertake global assignments. The selection of and the capability to attract the right candidates is critical to successful expatriation (Kandogan, 2018). Given the context of global war for talent and boundary-less labor market, it is important to understand how families can influence the Japanese expatriates' decision-making process of expatriation so that practitioners can act upon the findings.…”
Section: Research Areas For the Preexpatriation Phasementioning
confidence: 99%